Hyperspectral Image Classification of Soils using Soft Computing Techniques (Journal of Pharmaceutical Negative Results, 2022)
In geotechnical engineering classification of soils is an important accept because to provide guidance about soils based on their experimental analysis. The classification of system can be done in various ways because one should not rely on empirical information for solving the problems. These soil types are classified based on their behavioural conditions and based on generalized information provided by the scientists, engineers and resource persons. Classification of soil type by visiting particular location is difficult so remote sensing images are used. The most widely used remote sensing method for classification of soils is hyperspectral image (HSI) technology. To classify HSI different soft computing techniques are applied and compared algorithms with their accuracies to know the best algorithm for classification of soil types.